An evaluation of executive functions, cognitive control and a neurocognitive profile of college binge drinkers - Banz, Barbara C., author; Davalos, Deana B., advisor; Chavez, Ernest, committee member; Troup, Lucy, committee member; Davies, Timothy, committee member (Colorado State University. Libraries, 2014)
Introduction: Binge drinking is a detrimental behavior which presents with consumption of large amounts of alcohol however, does not present with symptoms of dependence. The college population is a unique group to investigate due to the neuroplasticity and development those in this cohort are undergoing. Specifically, this age group is experiencing a natural period of neural immaturity specific to the prefrontal cortex. In addition to being identified by the personal, physical, and academic detriments caused by binge drinking, it was hypothesized this population of binge drinkers could be categorized with a neurocognitive profile which varies from their non-drinking peers. Participants: One hundred and ninety seven Colorado State University students were recruited and categorized in to different levels of binge alcohol consumption on non-drinkers based on two self-report measures. Method: Alcohol consumption was evaluated through a sex based questionnaire and the Alcohol Use Disorder Identification Test. Neurocognitive performance was assessed through six tasks: Wisconsin Card Sorting Test, Delay Discounting Task, One Touch Stockings of Cambridge, Trail Making Task (A and B), the Behavioral Rating Inventory of Executive Function, and the Dysexecutive Questionnaire. Results: An initial MANOVA was used to assess differences between non-drinkers and binge drinkers, showing no significance, F (12, 19) = 1.96, p = 0.09. A secondary MANOVA was used to evaluate differences across different categories of binge drinkers and non-drinkers, where significance was noted, F (36, 92.32) = 1.56, p = 0.045. The post hoc tests suggest the significance of this relationship was due to poorer performance on the WCST by binge drinkers, F (3, 42) = 3.27; p = 0.03. Conclusions: Though the deficits were not as vast as hypothesized, the inability for binge drinkers to complete an equal number of categories in the WCST as their non-drinking peers holds interesting conclusions. Those which are discussed relate to binge drinkers' inefficient self-reporting of executive functioning performance, as well as allowing us to possibly understand why we see differences in binge drinkers' perception of alcohol outcomes and their personal self-efficacy with alcohol consumption.
Keywords: binge drink; alcohol; college; executive function; neurocognitive